2014
DOI: 10.1519/jsc.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Cardiorespiratory Fitness Assessment for Firefighters

Abstract: Currently, a submaximal protocol is used to measure cardiorespiratory fitness in firefighters by estimating their true aerobic capacity (V[Combining Dot Above]O2max); however, this submaximal test has not been cross-validated among firefighters. Thirty firefighters (85% male, 15% female), completed the submaximal protocol and the maximal (Bruce) treadmill protocol on separate occasions. Pearson's correlation analyses between the submaximal and Bruce protocol revealed a significant moderate positive correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The Bruce Protocol is a 7-stage graded exercise treadmill test that measures the ability to perform moderately strenuous exercise over an extended time and is used to estimate maximal aerobic capacity [ 62 ]. This protocol has been used within the health and wellness program for many years to produce historical normative data and has also been adopted before for aerobic testing in firefighters [ 63 , 64 , 65 , 66 ]. Standard procedures were followed for this test [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bruce Protocol is a 7-stage graded exercise treadmill test that measures the ability to perform moderately strenuous exercise over an extended time and is used to estimate maximal aerobic capacity [ 62 ]. This protocol has been used within the health and wellness program for many years to produce historical normative data and has also been adopted before for aerobic testing in firefighters [ 63 , 64 , 65 , 66 ]. Standard procedures were followed for this test [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…This protocol has been used within the health and wellness program for many years to produce historical normative data and has also been adopted before for aerobic testing in firefighters [ 63 , 64 , 65 , 66 ]. Standard procedures were followed for this test [ 62 , 63 , 64 , 65 , 66 ]. Following a 1 min warm-up on the treadmill at a speed of 2.7 km per hour (km/h) with a 0% grade, the Bruce Protocol was initiated, prompting firefighters to begin stage 1 at a speed of 2.7 km/h with a 10% grade.…”
Section: Methodsmentioning
confidence: 99%
“…Although presented study aimed on determination of isokinetic and explosive strength, cardiorespiratory fitness is also an important component of good health-related physical fitness. A low level of cardiovascular fitness is associated with risk factors of cardiovascular diseases [43], such as hypertension, dyslipidaemia, and obesity, which are leading cause of on-duty death or disability [44] in firefighters. Obesity is associated with a sedentary job and lack of movement, irregular sleeping, unbalanced and irregular nutrition, and effect of 24 h shifts as factors threatening first-line firefighters [45].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Dolezal et al concluded that the WFI protocol had a tendency to overestimate CRF among those who were considered less fit while underestimating those who were considered high fit (i.e., 11% error margin) [56]. Moreover, it was noted that the present policies for measuring CRF among firefighters should be reevaluated, and a more robust approach is likely needed [54,57]. Fire departments are beginning to utilize alternative field-based protocols to assess CRF among firefighters, including maximal effort intermittent shuttle run tests (e.g., 30-15 intermittent fitness test (IFT)), which may simulate the discontinuous physical efforts frequently utilized on the fireground, or continuous shuttle run (beep) tests; both of which allow for multiple firefighters to be tested concurrently.…”
Section: Physical Health Countermeasure: Clinical and Fitness Assessm...mentioning
confidence: 99%
“…The most accurate way to assess CRF is to measure oxygen consumption with a gas analyzer during a maximal effort on a treadmill or cycle ergometer. CRF assessments might not always be feasible due to expense, time, and requirements for proper exercise testing equipment [56][57][58]. Interestingly, Yang et al conducted a retrospective longitudinal cohort study among 1104 firefighters from 10 fire departments over a 10-year period [59].…”
Section: Physical Health Countermeasure: Clinical and Fitness Assessm...mentioning
confidence: 99%